Classical Study of Exponential Function and Their Applications - Thakur, Aayush; Das, Rakesh; Sah, Shivam; Sahani, Suresh Kumar; Sahani, Kameshwar (Lembaga Yasin AlSys, 2024)
The exponential function as a mathematical concept plays an important role in the corpus of mathematical knowledge, but unfortunately students have problems grasping it. Paper exposes example of exponential example of exponential function application in real world. One of the most prevalent application of exponential function involves growth and decay models. Exponential growth and decay show up in a host of natural application. From population Growth and continuously compounded interest to radioactive decay and Newton’s law of cooling, exponential function are ubiquitous in nature. In this section, we examine exponential growth and decay in the context of some of the application. In the preceding section, we examined a population growth problem in which the population grew at a fixed percentage each year. In that case, we found that the population can be described by exponential function. A similar analysis will show that any process in which a quantity grows by a fixed percentage each year can be modeled by an exponential function. Compound interest is good example of such a process. This work is motivated by the works of [1-15, 22]. Other example of exponential function are bacterial growth, bacterial decay, population decline, are obtained in this project.